2014
DOI: 10.2140/gt.2014.18.1115
|View full text |Cite
|
Sign up to set email alerts
|

The period-index problem for twisted topologicalK–theory

Abstract: We introduce and solve a period-index problem for the Brauer group of a topological space. The period-index problem is to relate the order of a class in the Brauer group to the degrees of Azumaya algebras representing it. For any space of dimension d , we give upper bounds on the index depending only on d and the order of the class. By the Oka principle, this also solves the period-index problem for the analytic Brauer group of any Stein space that has the homotopy type of a finite CW-complex. Our methods use … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
104
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(104 citation statements)
references
References 42 publications
0
104
0
Order By: Relevance
“…Because the composition [3]. This already shows that the étale index is different, in general, from the period.…”
Section: Recall That a Sequencementioning
confidence: 80%
See 1 more Smart Citation
“…Because the composition [3]. This already shows that the étale index is different, in general, from the period.…”
Section: Recall That a Sequencementioning
confidence: 80%
“…It is a major open problem in the theory of Azumaya algebras, even when X D Speck, to determine the possible pairs .per.˛/;ind.˛// for˛2 Br K et .X/ where X is fixed, or where the dimension of X is fixed. For an introduction to what is known and for further references, see [3,Section 1].…”
mentioning
confidence: 99%
“…This paper is a sequel to , in which Antieau and Williams initiated the study of the topological period–index problem. Given a path‐connected topological space X, let Br(X) be the topological Brauer group defined in , whose underlying set is the Azumaya algebras modulo the Brauer equivalence: A0 and A1 are called Brauer equivalent if there are vector bundles E0 and E1 such that scriptA0Endfalse(E0false)scriptA1Endfalse(E1false).The multiplication is given by tensor product. Remark In its full generality, Brauer group can be defined for any locally ringed topos.…”
Section: Introductionmentioning
confidence: 99%
“…Let per(α) denote the order of α as an element of the group H3false(X;double-struckZfalse), then Serre also showed that per(α)|r, for all r such that there is a PUr‐torsor over X associated to α in the way described above. Let ind(α) denote the greatest common divisor of all such r, then in particular we have per(α)|ind(α).Furthermore, Antieau and Williams showed the following Theorem Let (X,R) be a locally ringed connected topos and let αBr(X,R). There exists a representative A of α such that the prime numbers dividing per(α) and deg(A) coincide.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation